2017
DOI: 10.1021/acs.analchem.7b01601
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Relationship between Expression and Functional Activity of Multidrug Resistance-Associated Protein 1 using Scanning Electrochemical Microscopy

Abstract: Cancer cells can develop multidrug resistance (MDR) after prolonged exposure to chemotherapeutic drugs, which is a severe impediment to successful treatment. MDR is typically associated with transmembrane proteins mediating efflux of administered drugs, thereby keeping their intracellular concentration below the threshold required to kill cells. Although expression assays based on flow cytometry and immunostaining have shown that multidrug resistance-associated protein 1 (MRP1) is prevalent in many cancer type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…P-gp is the most characterized MDR transporter and has been recognized as a target to overcome MDR in cancer therapy 28,29. The MRPs, especially MRP1, promote resistance against chemotherapeutics 30. Our in vivo study showed that NPRL2 decreased the expression of P-gp and MRP1.…”
Section: Discussionmentioning
confidence: 60%
“…P-gp is the most characterized MDR transporter and has been recognized as a target to overcome MDR in cancer therapy 28,29. The MRPs, especially MRP1, promote resistance against chemotherapeutics 30. Our in vivo study showed that NPRL2 decreased the expression of P-gp and MRP1.…”
Section: Discussionmentioning
confidence: 60%
“…To exclude the interference of NMs and debris, the solutions with each concentration and treatment were gated out of the analysis, i.e., for each cell exposure concentration, there was an equivalent exposure concentration without cells that was used for gating. Doublets were excluded using FSC-H versus FSC-A analysis [27]. Amoebocytes and eleocyte populations were identified as described in Engelmann et al [28].…”
Section: Introductionmentioning
confidence: 99%
“…SECM has since been applied to kinetic studies, surface and interface studies, microstructure fabrication . SECM has also found applications as a bioanalytical tool for cellular imaging, membrane transport,16b,17 neurotransmitter release, multidrug resistance,16c,16d,19 ROS and RNS mapping,16i,20 and cellular redox processes 16g,21…”
Section: Introductionmentioning
confidence: 99%